Optimasi Konsentrasi Asetosiringon dan Higromisin dalam Transformasi Genetik Padi Fatmawati dengan Perantaraan Agrobacterium tumefaciens - Sisharmini, Atmitri; Purwoko, Bambang Sapta; Khumaida, Nurul; Trijatmiko, dan Kurniawan Rudi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
Protocols for genetic transformation of rice have been widely developed, however the protocols are not universal and inapplicable for all types of rice plants directly. Transformation protocol on rice cv. Fatmawati needs to be developed to generate transgenic lines. The present research was carried out to optimize genetic transformation protocol in rice cv. Fatmawati mediated by Agrobacterium tumefaciens harboring pCambia1301 construct using immature embryo as an explant. The experiment was arranged in a completely randomized design. Factors influencing efficiency of transformation, i.e., sensitivity of callus to hygromycin antibiotic, acetosyringone concentration used in cultivation medium, hygromycin concentration for transformant selection were optimized. The results showed that genetic transformation of rice cv. Fatmawati mediated by A. tumefaciens using immature embryos have been successfully carried out with several parameters. Addition of 100 µM acetosyringone in co-cultivation medium and 30 mg L-1 hygromycin for transformant callus selection were optimal for genetic transformation of rice cv. Fatmawati mediated by A. tumefaciens. Transformation efficiency was found to be 7.84% based on the lines carrying the hpt gene. This result would be a valuable reference in genetic transformation of rice cv. Fatmawati using target genes.Keywords: immature embryo, Oryza sativa, pCambia1301, transformation efficiency